Frequency of Hypotension During Conventional or Asymmetric Hyperbaric Spinal Block. Issue 3 (1st May 1999) - Casati, Andrea; Fanelli, Guido; Aldegheri, Giorgio; Colnaghi, Eleonora; Casaletti, Elisabetta; Cedrati, Valeria; Torri, Giorgio
Abstract : Background and Objectives: The purpose of this randomized, double-blind study was to evaluate if use of an asymmetric spinal block affects the incidence of hypotension during spinal anesthesia. Methods: With Ethical Committee approval and patient consent, 120 patients undergoing lower limb surgery were placed in the lateral position with the side to be operated on dependent, and received 8 mg 0.5% hyperbaric bupivacaine through a 25-gauge Whitacre spinal needle. Patients were randomized to one of two groups: (a) local anesthetic was injected with barbotage through a cranially directed needle orifice, then patients were immediately turned to supine (conventional, n = 60); (b) local anesthetic was injected without barbotage with the needle orifice turned toward the dependent side, then the lateral position was maintained for 15 minutes (unilateral, n = 60). A blind observer recorded noninvasive hemodynamic variables, as well as loss of cold and pinprick sensation and motor block on both sides. Results: In the unilateral group, 31 patients (52%) showed a unilateral loss of cold sensation and 48 patients (80%) had no motor block on the nondependent side for the duration of the study, whereas all conventional patients had bilateral distribution of spinal block ( P < .0001). The onset time and two-segment regression of sensory block on the dependent side were more rapid in the conventional group (18 ± 7 minutes and 60 ± 18 minutes) than in the unilateral group (22 ± 8 minutes and 67 ± 19 minutes) ( P <.05 and P <.05, respectively). The incidence of hypotension (SAP decrease >30% from baseline) was higher in the conventional (22.4%) than unilateral group (5%) ( P < .01). The maximum percentage changes from baseline values of systolic arterial blood pressure and heart rate were greater in conventional group (−28% ± 16% and −19% ± 10%) than in unilateral group (−8% ± 16% and −12% ± 18%) ( P < .0001 and P < .01, respectively). Conclusions: Achieving an asymmetric distribution of spinal block by injecting a small dose of 0.5% hyperbaric bupivacaine through a Whitacre spinal needle into patients placed in the lateral position for 15 min reduces the incidence of hypotension during spinal anesthesia.